The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jamr-09-2018-0076
|View full text |Cite
|
Sign up to set email alerts
|

Understanding succession planning as a combating strategy for turnover intentions

Abstract: Purpose Considerable research has linked leaders’ development practices to employee performance, but little research has concentrated on how succession planning minimizes the turnover intentions. The purpose of this paper is to investigate the impact of succession planning on turnover intentions among banking professionals. Moreover, the authors examine whether succession planning enhances the employee job security and creates career attitude that mitigates the risk of employee turnover intentions. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 45 publications
(38 reference statements)
0
40
0
8
Order By: Relevance
“…Webb, Diamond-Wells, and Jeffs (2017) stated that succession planning improves the professional development of employees, which in turn enhances their performance. Ali and Mehreen (2018) investigated the association between succession planning and turnover intentions in banking employees and found that succession planning significantly minimized turnover intentions. Perrenoud and Sullivan (2017) found that succession planning improved employee satisfaction, and Munro (2017) stated that succession planning had become a critical driver of organizational and leader renewal.…”
Section: Literature Review Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Webb, Diamond-Wells, and Jeffs (2017) stated that succession planning improves the professional development of employees, which in turn enhances their performance. Ali and Mehreen (2018) investigated the association between succession planning and turnover intentions in banking employees and found that succession planning significantly minimized turnover intentions. Perrenoud and Sullivan (2017) found that succession planning improved employee satisfaction, and Munro (2017) stated that succession planning had become a critical driver of organizational and leader renewal.…”
Section: Literature Review Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Davenport et al, (2012), mengungkapkan bahwa succession planning memainkan peran penting untuk dapat meningkatkan retensi karyawan sehingga tingkat turnover karyawan menjadi lebih rendah. Ali & Mehreen, (2019), succession planning meningkatkan loyalitas karyawan, keterlibatan karyawan, dan yang terpenting dapat mengembangkan individu yang terampil dan berbakat dalam organisasi. Reeves, (2010), succession planning berperan dalam memastikan bahwa kesuksesan organisasi akan berlanjut meski individu atau pemimpin yang saat ini terlibat sudah tidak ada.…”
Section: Pendahuluanunclassified
“…(Z. Ali & Mehreen, 2019;Davenport et al, 2012;Govender, 2010;Mehrabani & Mohamad, 2011;Nissan & Eder, 1995). Ali, Omar, & Amin, (2013) menemukan bahwa penilaian kinerja (performance appraisal) dan perencanaan suksesi (succession planning) secara signifikan terkait dengan kinerja karyawan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations